2002
DOI: 10.1093/annonc/mdf189
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine is effective in relapsed or refractory aggressive non-Hodgkin’s lymphoma

Abstract: Bendamustine as a single agent is effective against aggressive lymphoma, even in cases of refractory disease. Further studies are warranted to determine the significance of bendamustine in the treatment of aggressive lymphomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 12 publications
3
49
0
Order By: Relevance
“…Previous phase II studies of monotherapy BM demonstrated impressive remission rates combined with good tolerability in relapsing and/or refractory non-Hodgkin's lymphoma (NHL) (Heider and Niederle, 2001;Bremer, 2002;Weidmann et al, 2002;Friedberg et al, 2004). Moreover, in combination with vincristine and prednisone (BOP), BM demonstrated higher 5-year survival rates (61 vs 46%) compared to cyclophosphamide containing standard regimen .…”
mentioning
confidence: 99%
“…Previous phase II studies of monotherapy BM demonstrated impressive remission rates combined with good tolerability in relapsing and/or refractory non-Hodgkin's lymphoma (NHL) (Heider and Niederle, 2001;Bremer, 2002;Weidmann et al, 2002;Friedberg et al, 2004). Moreover, in combination with vincristine and prednisone (BOP), BM demonstrated higher 5-year survival rates (61 vs 46%) compared to cyclophosphamide containing standard regimen .…”
mentioning
confidence: 99%
“…Bendamustine as a single agent is effective against aggressive lymphoma, even in cases of refractory disease. In a phase II study of 21 patients reported by Weidmann et al 22 with relapsed or refractory high-grade NHLs, 18 were evaluated for response and toxicity with 10 of these refractory to previous chemotherapy. Three patients achieved a complete response (at 6, 8, and 22 months) and five achieved partial response (three at 2 months, one at 3 months, and one at 10 months); the total response rate of evaluated patients was 44% (8 out of 18, 38% of all patients).…”
Section: Discussionmentioning
confidence: 99%
“…Three patients achieved a complete response (at 6, 8, and 22 months) and five achieved partial response (three at 2 months, one at 3 months, and one at 10 months); the total response rate of evaluated patients was 44% (8 out of 18, 38% of all patients). 22 Subsequently in 2011, Weidman et al also reported a phase II study of bendamustine and rituximab as first-line treatment in elderly patients ($80 years) with aggressive B-cell lymphomas who were not eligible for R-CHOP or who did not agree to aggressive treatment. 23 Thirteen patients were assessed for response.…”
Section: Discussionmentioning
confidence: 99%
“…Bendamustine, originally designed to have both alkylating 1) and antimetabolite properties, 2) has shown clinical activity against various human malignancies including non-Hodgkin's lymphoma [3][4][5][6][7] and chronic lymphocytic leukemia. 8) According to the National Comprehensive Cancer Network (NCCN) guidelines for patients with non-Hodgkin's lymphoma, 9) bendamustine alone or bendamustine with rituximab is used for patients with follicular lymphoma or mantle cell lymphoma.…”
Section: Decrease In Venous Irritation By Adjusting the Concentrationmentioning
confidence: 99%